Composition of dental plaque formed in the presence of sucrose and after its interruption - Cury Jaime Aparecido; Marques Aline Soler; Tabchoury Cíntia Pereira Machado; Del Bel Cury Altair Antoninha (Fundação Odontológica de Ribeirão Preto, 2003)
Since dental plaque reservoirs of fluoride (F), calcium (Ca) and inorganic phosphorus (Pi) are susceptible to decreases in pH, this in situ crossover study was conducted to test the hypothesis that the low concentration of these ions in plaque, formed in the presence of sucrose, could be attributed merely to the fermentation of this sugar. Eleven volunteers wore palatal appliances containing 6 human enamel blocks during two stages. In each stage, the treatments were either 20% sucrose solution or distilled deionized water, which were dripped onto the blocks 8 times a day. After 28 days, in each stage, the dental plaque formed on two blocks was collected, the treatment was inverted and after a further 24 and 48 h, the biofilm formed was collected from the other blocks. The concentration of acid-soluble F, Ca and Pi, and the concentration of insoluble polysaccharide (IP) were determined in the dental plaque. Statistically lower concentrations of F, Ca and Pi, and a higher concentration of IP were found in the 28-day biofilm formed in the presence of sucrose than in its absence; after the treatment inversion the change in F, Ca and Pi was not statistically significant, but the IP concentration changed significantly. The hypothesis was rejected because change in concentration of F, Ca and Pi is not due to fermentation of the sucrose.